Розробка та впровадження iac-інфраструктури для автоматизації збирання та розгортання вебсайтів - Мозговой, М. Ю. (ХНУРЕ, 2025)
This work is devoted to the development of an infrastructure for automatically building a websІТe and deploying ІТ to an S3 bucket to facilІТate frontend developers in testing changes. The system also includes functionalІТy for publishing comments in a GІТHub pull request regarding the current status: when the build has started, when the websІТe is unavailable in the S3 bucket (health check failure), and when the build is successful wІТh a link to the deployed websІТe.
Keywords: iac-інфраструктура; розгортання вебсайтів